Real‐time segmentation of various insulators using generative adversarial networks. Issue 5 (26th February 2018) - Chang, Wenkai; Yang, Guodong; Yu, Junzhi; Liang, Zize
Abstract : The conventional inspection of fragile insulators is critical to grid operation and insulator segmentation is the basis of inspection. However, the segmentation of various insulators is still difficult because of the great differences in colour and shape, as well as the cluttered background. Traditional insulator segmentation algorithms need many artificial thresholds, thereby limiting the adaptability of algorithms. A compact end‐to‐end neural network, which is trained in the framework of conditional generative adversarial networks, is proposed for the real‐time pixel‐level segmentation of insulators. The input image is mapped to a visual saliency map, and various insulators with different poses are filtered out at the same time. The proposed two‐stage training and empty samples are also used to improve the segmentation quality. Extensive experiments and comparisons are performed on many real‐world images. The experimental results demonstrate superior segmentation and real‐time performance. Meanwhile, the effectiveness of the proposed training strategies and the trade‐off between performance and speed are analysed in detail.